Optimizing PDAM In Drinking Water Management Medan City - Fitri R (Bandar Lampung University (UBL), 2017)
Water resources are one of the important natural resources because it is the main thing for the consumption and sanitation of human, water as transportation facilities in the world, recreation facilities, and irrigation water needs. On the other, excess water resources - floods - can result in heavy damage and loss of human life. Water as a hydrosphere environment in the global scale, unevenly over the earth so its abundance somewhere varies with time and hydrological cycles. Finally, in the use of water resources, humans pollute much of the available water and degrade it. That it is no longer suitable for all types of utilization. In obtaining clean water that is feasible and safe for consumption (especially for drinking), there needs to be a processing from raw water to water drink. Water treatment can be started by using a simple system and can also with a complex processing, according to the level of necessary needs depending on the quality of raw water to be processed. The lower the water quality, the higher the required level of processing. Medan one of Metropolitan city in Indonesia. Medan city includes three big cities in Indonesia after Jakarta and Surabaya. This is very influential in acceleration of the development Medan and the province of North Sumatra in general. PDAM Tirtanadi which is one of the regional companies owned by North Sumatra. It is engaged in the provision of clean water and operated efficiently with the support of adequate technology for serves the needs of clean water in Medan city and surrounding areas